Mengembangkan Universitas Islam Negeri (UIN) Alauddin Makassar Berbasis Kapabilitas Organisasi - Muhammad Yusuf Rahim (AL-Fikr, 2013)
One of steps in improving the quality of a higher education or a university such as UIN Alauddin Makassar is by implementing various strategic movements, for example an institutional change. UIN Alauddin, formerly known as ‘State Islamic Institute (IAIN) of Alauddin Makassar’. The next development, in 2005, the institute changed its status into a university. Changes in the organization's environment, a shift in perspectives about the organization and its people challenge the organization to develop forward. Organization is alive, growing and able to demonstrate organisms, related to one another, where both characters can be described and measured. Basically, organizational capability is the ability of the organization to implement its purposes and functions in achieving specific goals setting previously. The ability of an organization could be measured from several aspects, for example: (1) leadership ability, (2) human resources, (3) facilities, infrastructure, and funding, and (4) the structural ability, organizational systems and the environment.